Examining the Differences in Intrinsic Motivation and its Interactions Based on Ego States Among B - School Students in Coimbatore - Priyadarshini, V.; Joseph, Jelsy (Prabandhan: Indian Journal of Management, 2013)
Management Institutes are striving hard to create workspaces that ensure a greater understanding, better relationships and a happier environment through improved individual, team and institutional performance. This could be attained by matching the students' needs and motives with those of the institutional requirements. However, the greatest challenge is the inability or the lack of desire to predict their needs and motives. Researchers in behavioral sciences have created various models that can help administrators in redesigning pedagogy, develop effective teams, and motivate staff to deliver outstanding results. This article further contributes to behavioral sciences by presenting a simple, three-level typology model to classify the personality of students based on Transactional Analysis ego states and predicting the Intrinsic Motivation factors that best matches with the ego state.